CULTURE-BOUND WORDS USED IN EVERYDAY COMMUNICATION BY YAKUTIAN OLD-TIMERS: ETHNOLINGUISTIC ASPECT - Zhondorova, Galina (Revista Inclusiones, 2020)
The article considers one segment of the linguistic world-image typical of Yakutian old-timers and reveals the concept of culture-bound words used in their everyday communication, as well as nominations of vehicles and working clothes. From the early 17th century, the Russian old-timers have been presumably living in small groups in a foreign-language environment of the Republic of Sakha (Yakutia) – this Arctic territory is one of the constituent entities of the Russian Federation. Old-timers are the oldest group of the Russian people inhabiting Siberia. This study is based on folklore and dialect linguistic materials collected from representatives of the ethnic group and reflected in the "Dictionary of the Russian sub-dialects used by Yakutian old-timers". The author of the article focuses on the structure of the lexical-semantic group of words denoting "clothes" and "vehicles", the description of their main characteristics and the identification of their linguistic representation in the Russian sub-dialects used by old-timers. The semantics of words reveals a close relationship between their lexical meanings and specific facts of life common to Yakutian oldtimers.